ChemInform Abstract: Influence of A1, 3 Strain on the Stereochemical Outcome of Acid‐Mediated Amido Cyclization in the Synthesis of 2‐(4‐Methoxyphenyl)‐3, 4‐(dihydroxy)piperidines. Issue 31 (14th July 2016) - Ramakrishna, Katakam; Jagadeesh, Yerri; Ramakrishna, K. V. S.; Rao, Joshi Laxmikanth; Rao, Batchu Venkateswara
Abstract: A straightforward synthesis of the title compounds is reported based on an acid‐mediated amido cyclization reaction as the key step.